High-gloss spraying-free scratch-resistant heat-resistant high-impact PMMA-ASA alloy material and preparation method thereof

Through the synergistic effect of specific formula systems and components, the defects of spray-free PMMA-ASA alloy materials in hardness, gloss, scratch resistance and heat resistance are solved, and the comprehensiveness of high-gloss black, heat resistance and impact resistance is achieved. performance.

CN119463394APending Publication Date: 2025-02-18SHANGHAI SHENGNUO NEW MATERIAL TECH CO LTD +2
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411714142.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing spray-free PMMA-ASA alloy materials have defects in hardness, gloss, scratch resistance and heat resistance, making it difficult to have ideal scratch resistance and good high-gloss black appearance, and the heat resistance is also poor.

Method used

By adopting specific formulation systems, including PMMA resins, ASA glue powders, modified SAN resins, liquid toughening agents, polyester copolymer silicones, black masterbatches and antioxidants, synergistically to toughen and harden matrix resins, The combination of modified SAN resin and styrene-N-phenylmaleimide copolymer, the lubricating effect of polyester copolymer silicone, and the structure and composition of latex particles, jointly improve the scratch resistance and heat resistance of the material. Sex and highlight black effects.

Benefits of technology

The comprehensive performance of PMMA-ASA alloy material with high gloss black, heat resistance and impact resistance is achieved, and the scratch resistance and heat resistance of the material are improved, while reducing processing energy consumption and improving injection molding and molding effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
  • Figure SMS_4
    Figure SMS_4
Patent Text Reader

Abstract

The invention relates to the technical field of high polymer materials, and particularly discloses a high-gloss spraying-free scratch-resistant heat-resistant high-impact PMMA-ASA alloy material and a preparation method thereof. The PMMA-ASA alloy material is prepared from the following components in parts by weight: 50 to 59.5 parts of matrix resin, 15 to 25 parts of ASA rubber powder, 15 to 25 parts of modified SAN resin, 0.4 to 1.5 parts of liquid flexibilizer, 1 to 3 parts of polyester copolymerized organic silicon, 2 to 4 parts of black master batch and 0.2 to 0.8 part of antioxidant. According to the prepared PMMA-ASA alloy material, under the synergistic effect of all the components, the scratch-resistant effect is achieved, and the comprehensive performance of high light black, heat resistance and impact resistance of the PMMA-ASA alloy is guaranteed. In addition, due to the lubricating effect of the organic silicon, the processing energy consumption of the PMMA-ASA alloy material can be further reduced, and the injection molding demolding effect can also be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of polymer materials, and more specifically, to a high-gloss, spray-free, scratch-resistant, heat-resistant, and high-impact PMMA-ASA alloy material and a preparation method thereof. Background Art

[0002] In order to increase the attractiveness and high-end feel of the car's exterior, it is often necessary to present a high gloss effect on the surface. This effect is generally not directly obtained through injection molding, but achieved through spraying technology. However, the spraying process not only increases costs, but may also have adverse effects on the environment. Given that the country is actively promoting environmental protection, it is particularly important to develop environmentally friendly materials that do not require spraying.

[0003] PMMA resin, also known as acrylic, is favored for its excellent optical properties, excellent mechanical properties, outstanding weather resistance and high tinting strength. Its surface hardness is also quite high and it has been widely used in the field of automobile manufacturing. ASA resin is an acrylonitrile-styrene-acrylic rubber copolymer that does not contain butadiene rubber. Its weather resistance is more than 10 times that of traditional ABS resin. ASA resin also has excellent mechanical and tinting properties, as well as excellent chemical corrosion resistance, so it is widely used in automotive exterior parts, such as grilles, pillars and triangles. The spray-free PMMA-ASA alloy material made by combining PMMA and ASA resin can be used to produce automotive exterior parts.

[0004] Regarding the above-mentioned related technologies, the inventors believe that although the spray-free PMMA-ASA alloy material has certain impact strength and weather resistance, it still has defects such as poor hardness and blackness, and it is difficult to have ideal scratch resistance and good high-gloss black appearance, and the heat resistance effect is also poor. Summary of the invention

[0005] In the related art, the spray-free PMMA-ASA alloy material still has the defects of poor hardness and glossiness, and it is difficult to have ideal scratch resistance and good high-gloss black appearance, and the heat resistance effect is also poor. In order to improve the above defects, the present application provides a high-gloss spray-free scratch-resistant, heat-resistant and high-impact PMMA-ASA alloy material and a preparation method thereof.

[0006] In the first aspect, the present application provides a high-gloss, spray-free, scratch-resistant, heat-resistant, and high-impact PMMA-ASA alloy material, which adopts the following technical solution: A high-gloss, spray-free, scratch-resistant, heat-resistant and high-impact PMMA-ASA alloy material comprises the following components in parts by weight: 50-59.5 parts of a base resin, 15-25 parts of an ASA rubber powder, 15-25 parts of a modified SAN resin, 0.4-1.5 parts of a liquid toughening agent, 1-3 parts of a polyester copolymer silicone, 2-4 parts of a black masterbatch and 0.2-0.8 parts of an antioxidant; the base resin comprises a PMMA resin, the modified SAN resin comprises a SAN resin and a styrene-N-phenylmaleimide copolymer; the liquid toughening agent comprises a MAAS rubber elastomer, an antioxidant and latex particles.

[0007] By adopting the above technical scheme, in the formula system selected in this application, the base resin is PMMA resin as the main component, and the components such as ASA rubber powder, liquid toughening agent, and modified SAN resin cooperate to play a toughening and hardening role on the base resin. SAN has good compatibility with PMMA, better hardness, heat resistance, and impact strength. Styrene-N-phenylmaleimide copolymer has greater rigidity and has a synergistic effect with SAN. The addition of the modified SAN resin prepared by the combination of the two can reduce the loss of hardness and heat resistance caused by ASA, which helps to improve the scratch resistance and heat resistance of PMMA-ASA alloy. Polyester copolymer silicone fully combines the excellent compatibility between polyester material and PMMA resin and the lubricating effect of silicone, promotes the film formation of silicone, reduces the migration and precipitation of silicone, and thus reduces the friction coefficient of the material surface. Under the synergistic effect of polyester copolymer silicone, SAN, and styrene-N-phenylmaleimide copolymer, the scratch resistance of PMMA-ASA alloy material has been effectively improved, so that scratches are not easy to penetrate the surface and will not be visible white. MAAS and latex particles in the liquid toughening agent participate in synergistic toughening and adjust the dispersion, morphology and size of the composite rubber. They can also act as compatibilizers and styrene-N-phenylmaleimide copolymers to improve the compatibility between the components, thereby improving the black and bright effect of PMMA-ASA alloy to a certain extent. In addition, due to the lubrication of silicone, the energy consumption of PMMA-ASA alloy material processing can be further reduced, and the injection molding demolding effect can also be improved.

[0008] Preferably, the modified SAN resin is composed of SAN resin and styrene-N-phenylmaleimide copolymer in a weight ratio of (50-65):(35-50).

[0009] By adopting the above technical scheme, the present application optimizes the raw material composition of the modified SAN resin. Within the above composition range, the modified SAN resin can cooperate with the ASA rubber powder and the liquid toughening agent to produce good toughening and hardening effects, and improve the scratch resistance and heat resistance of the PMMA-ASA alloy.

[0010] Preferably, the components of the black masterbatch include SAN resin and carbon black.

[0011] Preferably, the polyester copolymer silicone is a double-terminated hydroxyl-terminated polyester copolymer silicone.

[0012] By adopting the above technical solution, the present application preferably selects the specific type of polyester copolymer silicone as double-terminated hydroxyl-terminated polyester copolymer silicone. The terminal hydroxyl group of the double-terminated hydroxyl-terminated polyester copolymer silicone can form a hydrogen bond with the ester group of PMMA, so it has good compatibility with PMMA resin, helps to reduce the migration and precipitation of silicone, reduces the friction coefficient of the material surface, and improves the scratch resistance of PMMA-ASA alloy.

[0013] Preferably, the average molecular weight of the double-terminal hydroxyl-terminated polyester copolymer silicone is 4000-6000.

[0014] By adopting the above technical scheme, the present application preferably selects the average molecular weight range of the double-terminal hydroxyl-terminated polyester copolymer silicone. The double-terminal hydroxyl-terminated polyester copolymer silicone selected within the above range can fully hinder the migration and precipitation of silicone, which helps to improve the scratch resistance of PMMA-ASA alloy.

[0015] Preferably, the glass transition temperature of the styrene-N-phenylmaleimide copolymer is 175-200°C.

[0016] By adopting the above technical scheme, the present application optimizes the glass transition temperature of styrene-N-phenylmaleimide copolymer. Styrene-N-phenylmaleimide copolymer can ensure good fluidity and dispersibility within this range, while showing good hardness and heat resistance, thereby improving the scratch resistance and heat resistance of PMMA-ASA alloy.

[0017] Preferably, the latex particles have a core-shell structure, the core of the core-shell structure is a butyl acrylate copolymer, and the shell of the core-shell structure is a copolymer of ethylene glycol dimethacrylate and allyl methacrylate.

[0018] By adopting the above technical scheme, the present application optimizes the structure and specific components of latex particles. The liquid toughening agent containing MAAS rubber elastomer and latex particles only needs to be added in a small amount to significantly improve the toughness of PMMA, synergistically reduce the dosage and impact of ASA, and does not affect the transparency, heat resistance and hardness of PMMA. It can also improve the high-gloss black effect of PMMA-ASA alloy.

[0019] Preferably, the base resin further comprises modified PMMA, and the modified PMMA is prepared according to the following method: (1) under nitrogen protection, adding nano-silicon dioxide into anhydrous ethanol and stirring and mixing, then adding the hydrolyzate of silane coupling agent, washing and filtering after heating in a water bath, and then vacuum drying to obtain silane-modified nano-silicon dioxide; the silane coupling agent includes vinyl triethoxysilane; (2) Under nitrogen protection, the modified nano-silica is mixed with a solvent, an MMA monomer, and an initiator, and heated to react to obtain PMMA-modified nano-silica; the PMMA-modified nano-silica is melt-blended with PMMA pellets, and then extruded and granulated to obtain modified PMMA.

[0020] By adopting the above technical scheme, the present application first uses a silane coupling agent to perform surface modification on nano-silicon dioxide, obtains silane-modified nano-silicon dioxide with vinyl groups on the surface, and then copolymerizes the silane-modified nano-silicon dioxide with MMA monomer under the action of an initiator, obtains PMMA-modified nano-silicon dioxide with PMMA groups grafted on the surface. The modified PMMA can be obtained by melt-blending the PMMA-modified nano-silicon dioxide with PMMA granules. The PMMA-modified nano-silicon dioxide in the modified PMMA has a good interface bonding effect with the PMMA resin, can absorb impact energy when impacted, and can also hinder the expansion of cracks, which helps to enhance the impact resistance of the PMMA-ASA alloy.

[0021] Preferably, the silane coupling agent further comprises a phenyl silane coupling agent.

[0022] By adopting the above technical scheme, the present application also modifies the nano-silica by means of a phenyl silane coupling agent. The phenyl group introduced in this way can cooperate with the styrene-N-phenylmaleimide copolymer to reduce the loss of hardness and heat resistance caused by ASA, reduce the tactile feel of scratches, and improve the scratch resistance of the PMMA-ASA alloy.

[0023] In a second aspect, the present application provides a method for preparing a high-gloss, spray-free, scratch-resistant, heat-resistant, and high-impact PMMA-ASA alloy material, using the following technical solution.

[0024] A method for preparing a high-gloss spray-free scratch-resistant, heat-resistant and high-impact PMMA-ASA alloy material comprises the following steps: (1) Weighing a base resin, ASA rubber powder, and a liquid toughening agent, stirring and mixing them to obtain a premix; (2) Weighing modified SAN resin, double-end hydroxyl-terminated polyester copolymer silicone, black masterbatch and antioxidant, mixing with the premix, and then melt blending through a twin-screw extruder, and then extruding, pelletizing and drying to obtain a high-gloss, spray-free, scratch-resistant, heat-resistant and high-impact PMMA-ASA alloy material.

[0025] By adopting the above technical scheme, the present application first uses matrix resin, ASA rubber powder and liquid toughening agent to prepare a premix, and then mixes the premix with the remaining components. After melt blending and subsequent treatment, a high-gloss, spray-free, scratch-resistant, heat-resistant and high-impact PMMA-ASA alloy material is obtained.

[0026] In summary, this application has the following beneficial effects: 1. The PMMA-ASA alloy material prepared in this application has achieved the effect of scratch resistance under the synergistic effect of various components, and also ensures the comprehensive performance of PMMA-ASA alloy of high gloss black, heat resistance and impact resistance. In addition, due to the lubrication effect of silicone, the processing energy consumption of PMMA-ASA alloy material can be further reduced, and the injection molding demolding effect can also be improved.

[0027] 2. The present application optimizes the structure and specific composition of latex particles, and the liquid toughening agent composed only needs to be added in a small amount to significantly improve the toughness of PMMA, synergistically reduce the dosage and impact of ASA, and does not affect the transparency, heat resistance and hardness of PMMA. It can also improve the high-gloss black effect of PMMA-ASA alloy.

[0028] 3. The present application defines modified PMMA as a component of the matrix resin. The PMMA-modified nano-silica in the modified PMMA has good interface bonding with the PMMA resin, can absorb impact energy when impacted, and can also hinder the expansion of cracks, which helps to enhance the impact resistance of the PMMA-ASA alloy.

[0029] 4. The present application also modifies the nano-silica by using a phenyl silane coupling agent. The phenyl group introduced in this way can cooperate with the styrene-N-phenylmaleimide copolymer to reduce the loss of hardness and heat resistance caused by ASA, reduce the tactile feel of scratches, and improve the scratch resistance of the PMMA-ASA alloy. DETAILED DESCRIPTION

[0030] The present application is further described in detail below in conjunction with embodiments, preparation examples and comparative examples. The raw materials involved in the present application can all be obtained commercially.

[0031] Preparation example of modified PMMA The following is an explanation using Preparation Example 1.

[0032] Preparation Example 1 In this preparation example, modified PMMA was prepared according to the following method: (1) Under nitrogen protection, 10 g of nano-silica (preserved at 100° C. for 12 h before use) was added to 100 mL of anhydrous ethanol and stirred for 30 min, and then 15 mL of a hydrolyzate of a silane coupling agent (the concentration of the silane coupling agent was 25 wt %, and the mixture was allowed to stand for 3 h after preparation) was added and stirred, and then the mixture was heated in a water bath at 70° C. for 4 h, washed and filtered, and then vacuum dried to obtain silane-modified nano-silica; in this step, the silane coupling agent was vinyl triethoxysilane; (2) Under nitrogen protection, the modified nano-silica was mixed with 100 mL of ethanol, 50 mL of MMA monomer, and 1% of the total weight of the initiator BPO, and heated at 80° C. for reaction for 3 h. After washing, filtering and drying, PMMA-modified nano-silica was obtained; the PMMA-modified nano-silica was melt-blended with PMMA granules (grade CM-205, Zhenjiang Chimei Chemical) at a weight ratio of 1:25, and then extruded and granulated to obtain modified PMMA.

[0033] Preparation Example 2 The difference between this preparation example and preparation example 1 is that the silane coupling agent is a mixture of vinyltriethoxysilane and phenyltriethoxysilane in a weight ratio of 2:3. Example

[0034] Examples 1-6 The following description is given by taking Example 1 as an example.

[0035] Example 1 In this embodiment, the base resin is PMMA resin (brand CM-205, Zhenjiang Chimei Chemical), the modified SAN resin is compounded by SAN resin (brand PN-128L100, Zhenjiang Chimei Chemical) and styrene-N-phenylmaleimide copolymer (brand MS-NIP, Nippon Electric Chemical) in a weight ratio of 50:50 (referred to as the compounding ratio in Table 1), and the glass transition temperature of styrene-N-phenylmaleimide copolymer (referred to as Tg in Table 1) is 185°C; the components of the liquid toughening agent (brand ZR02.5.110, Shenzhen Xinhengli Technology) include MAAS rubber elastomer, antioxidant and latex particles, and MAAS is a methyl methacrylate-butyl acrylate-acrylonitrile-styrene tetra-graft copolymer. The carbon black content of the black masterbatch (brand name XP6399D, Cabot) is 30 wt %; the polyester copolymer silicone is a double-terminated hydroxyl-terminated polyester copolymer silicone with an average molecular weight of 4000 (brand name SG-600A, Zhejiang Jiahua Fine Chemical).

[0036] This embodiment provides a high-gloss, spray-free, scratch-resistant, heat-resistant, and high-impact PMMA-ASA alloy material, including the following components: 59 kg of matrix resin, ASA rubber powder (brand 80DA, Shanghai Shengnuo Xinchuang Material Technology) 15kg, modified SAN resin 20kg, liquid toughening agent 0.4kg, polyester copolymer silicone 1kg, black masterbatch 2kg and antioxidant 0.2kg (brand AT-215, Saint-LeCoultre).

[0037] This embodiment provides a method for preparing a high-gloss spray-free scratch-resistant, heat-resistant and high-impact PMMA-ASA alloy material, comprising the following steps: (1) Weighing PMMA, ASA rubber powder and liquid toughening agent, stirring and mixing to obtain a premix; (2) Weighing modified SAN resin, double-end hydroxyl-terminated polyester copolymer silicone, black masterbatch and antioxidant, mixing with the premix, and then melt blending through a twin-screw extruder, and then extruding, pelletizing and drying to obtain a high-gloss, spray-free, scratch-resistant, heat-resistant and high-impact PMMA-ASA alloy material; in this step, the temperature of the extruder 1-2 zone is 220° C., the temperature of the 3-5 zone is 240° C., the temperature of the 6-7 zone is 235° C., the die head temperature is 240° C., and the screw speed is 250 rpm.

[0038] As shown in Table 1, the differences between Examples 1-6 mainly lie in the different raw material ratios and raw material performance parameters.

[0039] Table 1 Raw material ratio and raw material performance parameters Example 7 The difference between this embodiment and embodiment 4 is that the base resin is a mixture of PMMA resin (brand name CM-205, Zhenjiang Chimei Chemical) and the modified PMMA of preparation example 1 in a weight ratio of 3:1.

[0040] Example 8 The difference between this embodiment and embodiment 7 is that the modified PMMA is prepared according to the method of preparation example 2.

[0041] Comparative Example Comparative Example 1 The difference between this comparative example and Example 1 is that the polyester copolymer silicone is replaced by an equal weight of PMMA resin.

[0042] Comparative Example 2 The difference between this comparative example and Example 4 is that the modified SAN resin is replaced by an equal weight of PMMA resin.

[0043] Comparative Example 3 The difference between this comparative example and Example 3 is that the liquid toughening agent is replaced by an equal weight of PMMA resin.

[0044] Comparative Example 4 The difference between this comparative example and comparative example 3 is that the modified SAN resin is replaced by an equal weight of PMMA resin.

[0045] Performance testing methods The PMMA / ASA alloy materials prepared in the embodiment and the comparative example were respectively injection molded into a high-gloss sample plate with a specification of 150*100*3 mm and a sample strip with a size of 80*10*4 mm, and the performance tests were carried out as test samples. The results are shown in Table 2.

[0046] 1. Scratch resistance The scratch resistance test was carried out according to GMW14688 standard, using an electric cross-scratch tester, with a scratch finger of 0.75 mm, a scratch speed of 1 m / min, and a load of 10 N. The smaller the color difference value △L, the better the scratch resistance.

[0047] 2. Notched impact strength Tested according to ISO 180 / 1A standard, impact energy is 2.75J, temperature is 23℃.

[0048] 3. Blackness L value According to GB / T 7921-2008 standard, the blackness L value is measured using a spectrophotometer. The smaller the value, the better the blackness.

[0049] 4. Surface gloss According to GB / T 8807-1988 standard test, the gloss meter, the higher the value, the better the gloss.

[0050] 5. Heat deformation temperature Tested according to GB / T 1634-2019 standard, load 1.82MPa, 120℃ / h.

[0051] 6. Vicat softening point Tested according to ISO 306 standard, test conditions are load 5kg, 50℃ / h.

[0052] In combination with Examples 1-6 and Table 2, it can be seen that the present application achieves the scratch resistance effect of the alloy not turning white and the scratches not being strong to the touch through the synergistic effect between the modified SAN resin, the liquid toughening agent, the polyester copolymer silicone and PMMA and ASA, and improves the surface quality of the alloy. At the same time, the alloy retains the heat resistance that is not inferior to that of pure PMMA, and also has high impact resistance, thereby obtaining a high-gloss spray-free scratch-resistant, heat-resistant and high-impact PMMA-ASA alloy material with relatively ideal performance.

[0053] Combining Example 1 and Comparative Example 1 with Table 2, it can be seen that in the absence of polyester copolymer silicone, although the surface hardness of the PMMA-ASA alloy is improved and the scratches are not deep, the ΔL reaches 0.65, the scratches will still be obviously white, and the scratch resistance requirement cannot be met.

[0054] Combining Example 4 and Comparative Example 2 with Table 2, it can be seen that without adding modified SAN resin, the scratches will not turn white, but the scratches will feel stronger, and the heat resistance of the alloy will decrease, the heat deformation temperature will decrease from 83°C of pure PMMA to 80°C, and the Vicat softening point will decrease from 105°C of pure PMMA to 101°C.

[0055] Combining Example 3 and Comparative Example 3 with Table 2, it can be seen that if no liquid toughening agent is added for synergy, the impact strength of the PMMA-ASA alloy is significantly reduced, and the blackness is reduced, and the ideal high-gloss black effect cannot be achieved.

[0056] Combining Example 3 and Comparative Example 4 with Table 2, it can be seen that if the modified SAN resin is further removed on the basis of Comparative Example 3, only the effect of no whitening on scratches can be achieved. Although the notched impact strength of the alloy is higher in this case, the surface highlight effect and heat resistance are significantly reduced.

[0057] It can be seen from Example 4 and Example 7 in combination with Table 2 that the notched impact strength measured in Example 7 is relatively high. This is because the PMMA-modified nano-silica in the modified PMMA has a good interface bonding effect with the PMMA resin, which can absorb impact energy when impacted and can also hinder the expansion of cracks, thereby enhancing the impact resistance of the PMMA-ASA alloy.

[0058] Combining Example 7 and Example 8 with Table 2, it can be seen that the color difference value ΔL measured in Example 8 is smaller, and the heat deformation temperature and Vicat softening point also increase slightly, indicating that the phenyl group introduced by the phenylsilane coupling agent and the styrene-N-phenylmaleimide copolymer synergistically reduce the loss of hardness and heat resistance caused by ASA, reduce the tactile feel of scratches, and improve the scratch resistance of the PMMA-ASA alloy.

[0059] The above embodiments are merely explanations of the present application and are not limitations of the present application. After reading this specification, those skilled in the art may make modifications to the embodiments of the present application without any creative contribution as needed. However, as long as they are within the scope of the claims of the present application, they are protected by the patent law.

Claims

1. A high-gloss, spray-free, scratch-resistant, heat-resistant, and high-impact PMMA-ASA alloy material, characterized in that: The invention comprises the following components in parts by weight: 50-59.5 parts of base resin, 15-25 parts of ASA rubber powder, 15-25 parts of modified SAN resin, 0.4-1.5 parts of liquid toughening agent, 1-3 parts of polyester copolymer silicone, 2-4 parts of black masterbatch and 0.2-0.8 parts of antioxidant; the base resin comprises PMMA resin, the components of the modified SAN resin comprise SAN resin and styrene-N-phenylmaleimide copolymer; the components of the liquid toughening agent comprise MAAS rubber elastomer, antioxidant and latex particles.

2. The high-gloss, spray-free, scratch-resistant, heat-resistant, and high-impact PMMA-ASA alloy material according to claim 1, characterized in that: The modified SAN resin is composed of SAN resin and styrene-N-phenylmaleimide copolymer in a weight ratio of (50-65):(35-50).

3. The high-gloss, spray-free, scratch-resistant, heat-resistant, and high-impact PMMA-ASA alloy material according to claim 2, characterized in that: The components of the black masterbatch include SAN resin and carbon black.

4. The high-gloss spray-free scratch-resistant, heat-resistant and high-impact PMMA-ASA alloy material according to claim 2 is characterized in that: The polyester copolymer silicone is a double-terminal hydroxyl-terminated polyester copolymer silicone.

5. The high-gloss spray-free scratch-resistant, heat-resistant and high-impact PMMA-ASA alloy material according to claim 4 is characterized in that: The average molecular weight of the double-terminal hydroxyl-terminated polyester copolymer silicone is 4000-6000.

6. The high-gloss spray-free scratch-resistant, heat-resistant and high-impact PMMA-ASA alloy material according to claim 2, characterized in that: The glass transition temperature of the styrene-N-phenylmaleimide copolymer is 175-200°C.

7. The high-gloss spray-free scratch-resistant, heat-resistant and high-impact PMMA-ASA alloy material according to claim 1, characterized in that: The latex particles have a core-shell structure, the core of the core-shell structure is a butyl acrylate copolymer, and the shell of the core-shell structure is a copolymer of ethylene glycol dimethacrylate and allyl methacrylate.

8. The high-gloss spray-free scratch-resistant, heat-resistant and high-impact PMMA-ASA alloy material according to claim 1, characterized in that: The components of the matrix resin also include modified PMMA, and the modified PMMA is prepared according to the following method: (1) under nitrogen protection, adding nano-silica to anhydrous ethanol and stirring and mixing, then adding a hydrolyzate of a silane coupling agent, washing and filtering after heating in a water bath, and then vacuum drying to obtain silane-modified nano-silica; the silane coupling agent includes vinyl triethoxysilane; (2) Under nitrogen protection, the modified nano-silica is mixed with a solvent, an MMA monomer, and an initiator, and heated to react to obtain PMMA-modified nano-silica; the PMMA-modified nano-silica is melt-blended with PMMA pellets, and then extruded and granulated to obtain modified PMMA.

9. The high-gloss spray-free scratch-resistant, heat-resistant and high-impact PMMA-ASA alloy material according to claim 8, characterized in that: The silane coupling agent further includes a phenyl silane coupling agent.

10. The method for preparing the high-gloss spray-free, scratch-resistant, heat-resistant and high-impact PMMA-ASA alloy material according to any one of claims 1 to 9, characterized in that: The following steps are involved: (1) Weigh the base resin, ASA rubber powder and liquid toughening agent, stir and mix them to obtain a premix; (2) Weighing the modified SAN resin, double-end hydroxyl-terminated polyester copolymer silicone, black masterbatch and antioxidant, mixing with the premix, and then melt-blending through a twin-screw extruder, and then extruding, pelletizing and drying to obtain a high-gloss, spray-free, scratch-resistant, heat-resistant and high-impact PMMA-ASA alloy material.

Citation Information

Cited By

  • High-gloss spraying-free weather-resistant PMMA / ASA alloy material as well as preparation method and application thereof

    CN120365680A

  • Spraying-free high-heat-resistance PMMA / ASA material and preparation method thereof

    CN121427233A